Intensity referencing in an extrinsic optical fiber temperature sensor - Apelsmeier, A.; Gleixner, R.; Shamonin, B.; Schmauß, Bernhard (Procedia Engineering, 2010)
Optical fiber sensors based on intensity measurement require some form of intensity referencing to avoid errors arising from parasitic losses. Known techniques of referencing such as balanced bridge, divided beam systems or two-wavelength referencing are not suitable for low-cost applications since they use relatively complicated optical components such as multiple LED sources, couplers, filters etc. In this work a novel method of referencing in an extrinsic optical fiber sensor system utilizing temperature dependence of absorption edge in a semiconductor crystal is described. The sensor system comprises a single LED source and no optical fiber junctions. The emission spectrum of an LED depends on its temperature. The reference is provided by controlling the temperature of an LED source and transmission measurements with different emission spectra. The entire process is controlled by a microprocessor unit. Performance of a sensor system is investigated and it is shown that the losses in connectors may be compensated for.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.LEH.intens
Keywords: Extrinsic optical fiber sensor; Intensity referencing; Temperature measurement; Absorption edge; Semiconductor; Hot-spot measurement